ASSISTED REPRODUCTIVE TECHNOLOGY AND ANTIPHOSPHOLIPID SYNDROME - J. Kh. Khizroeva; T. M. Mashkova (IRBIS LLC, 2016)
The antiphospholipid antibodies (APA) exert multiple effects on the hemostasis system causing damage to all of its protective components including the endothelial barrier, natural anticoagulant function and endogenous fibrinolysis and activating the platelet phase of hemostasis, which is associated with numerous obstetrical complications andinfertility. The question is, what is the frequency of circulating APA in women who underwent IVF failure and whether there is a relationship between the presence of APA and poor reproduction outcome? This study aimed at elucidating the effect of the presence of APA on the outcomes of assisted reproductive technology (ART). A total of 267 women diagnosed with infertility and planning to get pregnant using the assisted reproductive technology (ART) have been examined. The results of examination demonstrated a high prevalence of circulating APA in a group of women who underwent IVF failure. High titers of APA were found in 42.1% of female patients who had undergone IVF failure. The fraction of women in whom fertility treatment using ART succeeded was 19.1%.